2020
DOI: 10.1111/brv.12616
|View full text |Cite
|
Sign up to set email alerts
|

The ecosystem services provided by social insects: traits, management tools and knowledge gaps

Abstract: Social insects, i.e. ants, bees, wasps and termites, are key components of ecological communities, and are important ecosystem services (ESs) providers. Here, we review the literature in order to (i) analyse the particular traits of social insects that make them good suppliers of ESs; (ii) compile and assess management strategies that improve the services provided by social insects; and (iii) detect gaps in our knowledge about the services that social insects provide. Social insects provide at least 10 ESs; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 371 publications
(331 reference statements)
1
58
0
1
Order By: Relevance
“…Termites play an important but under-recognized role in the functioning of tropical ecosystems (Bonachela et al, 2015;Ashton et al, 2019;Elizalde et al, 2020). Though best known as pests, fewer than 10% of the 3,000 termite species are categorized as such (Rouland-Lefèvre, 2011), while the majority are integral in carbon and nutrient cycling, breaking down wood, soil, grass and leaf litter.…”
Section: Introductionmentioning
confidence: 99%
“…Termites play an important but under-recognized role in the functioning of tropical ecosystems (Bonachela et al, 2015;Ashton et al, 2019;Elizalde et al, 2020). Though best known as pests, fewer than 10% of the 3,000 termite species are categorized as such (Rouland-Lefèvre, 2011), while the majority are integral in carbon and nutrient cycling, breaking down wood, soil, grass and leaf litter.…”
Section: Introductionmentioning
confidence: 99%
“…These groups are rarely evaluated, including in biogeographical analyses (Cardoso et al, 2020), yet they are highly significant due to their hyperdiversification and broad distributions (Peters et al, 2017). Furthermore, they have special economic value, considering the ecosystem services they provide, such as pollination and secondary seed dispersal (Elizalde et al, 2020). They are also of high conservation value in terms of environmental well‐being and are irreplaceable to ecological integrity (Samways et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…bioindicators, recreation) (MEA, 2005;Noriega et al, 2018). One review of ESs by insects identified 42 specific roles (Noriega et al, 2018); another recent review of the ESs of social insects identified 10 roles (Elizalde et al, 2020). Here we use the same approach to identify 10 ways through which aculeate wasps (solitary and social) provide ESs (Fig.…”
Section: Introductionmentioning
confidence: 99%